2009
DOI: 10.4081/ijas.2009.259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium propionate by different numbers of applications in first week postpartum of dairy cows on hypocalcemia, milk production and reproductive disorders

Abstract: This study was conducted to evaluate effects of calcium propionate on hypocalcemia, dry matter intake, body condition score, milk production and reproductive disorders in dairy cows. Twenty four multiparous Holstein cows were sorted by parity, body condition score (BCS) in close-up period and season of calving and assigned to one of the three treatments. The cows in treatment 1 (T1) received two drenches at calving and 24h after calving. The cows in treatment 2 (T2) received three drenches at calving, 24h afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
2
4
0
1
Order By: Relevance
“…This hypothesis is supported by the results obtained by these authors group [1], whereas glycemia had negative correlation (r = -0,39; P < 0.01) with milk solids not fat, and despite of non-significance with milk production (r = -0.17) even among animals with normal glycemic levels. Similar results were also reported by other authors in animals supplemented with calcium salts of fatty acids [14] and in animals supplemented with calcium propionate [11].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This hypothesis is supported by the results obtained by these authors group [1], whereas glycemia had negative correlation (r = -0,39; P < 0.01) with milk solids not fat, and despite of non-significance with milk production (r = -0.17) even among animals with normal glycemic levels. Similar results were also reported by other authors in animals supplemented with calcium salts of fatty acids [14] and in animals supplemented with calcium propionate [11].…”
Section: Discussionsupporting
confidence: 92%
“…As propionate is produced by ruminal fermentation and is the principal source for gluconeogenesis in peri partum cows, it lowered level of BHBA in the propionate-supplemented group [24]. Propionate stimulates insulin secretion, and it suppress the non-steroidal fatty acids [11], moreover, it leads to a lowered transport of fatty acid to mitochondria [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent milk fever, calcium propionate is usually administered orally around the time of the calving of cows. Kara et al [67] found that giving cows two drenches (each drench contained 0.68 kg calcium propionate) at calving and 24 h after calving was beneficial in treating milk fever. In summary, calcium propionate can act as a source of calcium to prevent milk fever in dairy cows during the perinatal period.…”
Section: Application As a Source Of Calcium To Prevent Milk Fever In mentioning
confidence: 99%
“…Guard (1996) estimou, em um mesmo rebanho, que as perdas anuais com a hipocalcemia subclínica foram cerca de quatro vezes maior do que a forma clínica, podendo apresentar uma prevalência de 20 a 54% (LEBLANC et al, 2006;REINHARDT et al,2011). Foi observado também que o risco de desenvolvimento de hipocalcemia aumenta em 9% com aumento da idade da vaca (LEAN; DEGARIS, 2010), podendo causar perdas de quase 2,9 kg leite/dia, até seis semanas pós-parto, sendo considerada uma doença economicamente importante (CHAPINAL et al, 2012 Outra consequência da hipocalcemia é a diminuição na ingestão de matéria seca, a qual leva a vários problemas metabólicos, como síndrome da vaca caída (BROZOS et al, 2011), retenção de placenta, prolapso do útero, deslocamento de abomaso (CHAPINAL et al, 2012), cetose (KARA et al, 2009) e redução no desempenho reprodutivo devido ao prolongamento do anestro pós-parto (MARTINEZ et al, 2012). Além disso, a hipocalcemia pode reduzir a capacidade das células do sistema imunológico em responder a estímulos, contribuindo para o desenvolvimento de infecções como a mastite e metrite (KIMURA et al, 2006;MARTINEZ et al, 2012).…”
Section: A Introduçãounclassified